The impact of Natura 2000 on forest management: a socio-ecological analysis in the continental region of the European Union - Susanne Winter; Lars Borrass; Maria Geitzenauer; Marieke Blondet; Ruth Breibeck; Gerhard Weiss; Georg Winkel (Biodiversity and Conservation, 2014)

Managing climate change in conservation practice: an exploration of the science–management interface in beech forest management - Jessica de Koning; Esther Turnhout; Georg Winkel; Marieke Blondet; Lars Borras; Francesca Ferranti; Maria Geitzenauer; Metodi Sotirov; Alistair Jump (Biodiversity and Conservation, 2014)
Scientific studies reveal significant consequences of climate change for nature, from ecosystems to individual species. Such studies are important factors in policy decisions on forest conservation and management in Europe. However, while research has shown that climate change research start to impact on European conservation policies like Natura 2000, climate change information has yet to translate into management practices. This article contributes to the on-going debates about science–society relations and knowledge utilization by exploring and analysing the interface between scientific knowledge and forest management practice. We focus specifically on climate change debates in conservation policy and on how managers of forest areas in Europe perceive and use climate change ecology. Our findings show that forest managers do not necessarily deny the potential importance of climate change for their management practices, at least in the future, but have reservations about the current usefulness of available knowledge for their own areas and circumstances. This suggests that the science–management interface is not as politicized as current policy debates about climate change and that the use of climate change ecology is situated in practice. We conclude the article by discussing what forms of knowledge may enable responsible and future oriented management in practice focusing specifically on the role of reflexive experimentation and monitoring.